Impact of incomplete pedigrees on inbreeding of Boran cattle in Kenya - Kios , David; Marle-Köster , Este Van; Visser , Carina; Kitilit , Jackson (African Journal of Education,Science and Technology (AJEST), 2017)
The livestock sector contributes 12% of the Gross Domestic Product (GDP) in Kenya. The sector plays a critical role in attainment of food security, employment, poverty eradication and traditional obligations among others. Beef production sub sector is dominated by the local breeds of cattle with a smaller percentage of exotic breeds kept in specialized farms. Most of the ranches prefer the Boran breed of cattle due to their resistance to diseases and ability to withstand high temperatures. Boran cattle play an important role in Kenya especially in the arid and semi arid lands (ASAL). Though animal recording is done by the Kenya Boran Cattle Breeders’ Society (KBCBS) through the Kenya stud book (KSB), misidentification of sires occur and or have not been recorded. The estimation of inbreeding assumes that all the stated relationships are accurate. Pedigree records are stored manually by the KSB resulting in a laborious process. Five thousand pedigree records from four stud herds were evaluated for inbreeding. The estimated inbreeding coefficient was low (0.0022) for records analyzed for a 40 year period in a closed nucleus breeding scheme. The high rate of sire misidentification (5-80%) among the four stud herds together with incomplete pedigree records may have caused the low inbreeding coefficient. The study shows the importance of proper records in determination of inbreeding which may be biased in the study herds. Inbreeding has been shown to reduce viability and performance of the livestock. This will impact negatively on the efforts to improve on food security and poverty eradication strategies.